Quandaries and Queries


Who is asking: Student
Level: Secondary


(x2-x2) = (x2-x2)
x(x-x) = (x+x)(x-x) [divide both sides by (x-x)]
x = x + x
x = 2x [divide both sides by x]
2 = x/x = 1

Where is the flaw in this problem? I cannot seem to find one for the life of me i thought it was the (x2-x2) = (x2-x2) factoring to x(x-x) = (x-x)(x+x), but it seems im wrong?




The flaw is in the second line. You said it explicitly

[divide both sides by (x-x)]

x - x = 0. You can't divide by zero.



Go to Math Central